2017
DOI: 10.1111/trf.14388
|View full text |Cite
|
Sign up to set email alerts
|

Age of platelet concentrates and time to the next transfusion

Abstract: BACKGROUND Storage time of platelet (PLT) concentrates has been negatively associated with clinical efficacy outcomes. The aim of this study was to quantify the association between storage time of PLT concentrates and interval to the next PLT transfusion for different types of PLT components, stored for up to 7 days and transfused to transfusion‐dependent hematooncology patients with thrombocytopenia. STUDY DESIGN AND METHODS From a cohort of patients from 10 major Dutch hospitals, patients were selected whose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Several observational studies in non-critically ill hematology patients reported improved post-transfusion increments when using fresh platelet concentrates stored for less than 3 days, though without any significant impact on the further incidence of bleeding events. [27][28][29][30][31] Finally, how may the present findings translate into improvement in platelet transfusion practices in the ICU? Few factors are likely amenable to specific interventions to improve the efficacy of transfusions, by increasing the dose of transfused platelets, and maybe controlling fever and avoiding thrombocytotoxic antibiotics.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Several observational studies in non-critically ill hematology patients reported improved post-transfusion increments when using fresh platelet concentrates stored for less than 3 days, though without any significant impact on the further incidence of bleeding events. [27][28][29][30][31] Finally, how may the present findings translate into improvement in platelet transfusion practices in the ICU? Few factors are likely amenable to specific interventions to improve the efficacy of transfusions, by increasing the dose of transfused platelets, and maybe controlling fever and avoiding thrombocytotoxic antibiotics.…”
Section: Discussionmentioning
confidence: 93%
“…Storage of platelet concentrates is limited to 5 days in France, and up to 7 days in other parts of the world, in order to prevent the development of storage lesions including bacterial proliferation and release of bioreactive substances. Several observational studies in non‐critically ill hematology patients reported improved post‐transfusion increments when using fresh platelet concentrates stored for less than 3 days, though without any significant impact on the further incidence of bleeding events …”
Section: Discussionmentioning
confidence: 99%
“…For a long time, it was true that PAS-stored platelets had a lower increment than plasma-stored ones. However, the reformulation of PAS-B to PAS-C already was a major improvement, for example prompting the Netherlands moving from 5-to 7-day storage of platelets in PAS [19]. This was based on the randomized clinical trial by Kerkhoffs et al [20], that studied transfusion efficacy in hemato-oncological patients, revealing that buffy coat-derived platelets in plasma, stored for up to 7 days after collection, had a 1-hour CCI of 17.1 ± 7.3, while those stored in PAS-C had a CCI of 15.3 ± 6.5, i.e.…”
Section: Corrected Count Increments Bleedingmentioning
confidence: 99%